Drive Bunch Train for the Dielectric Trojan Horse Experiment at the Argonne Wakefield Accelerator - Gerard Andonian; Nathan Burger; Nathan Cook; Scott Doran; Tara Hodgetts; Seongyeol Kim; Gwanghui Ha; Wanming Liu; Walter Lynn; Nathan Majernik; John Power; Alexey Pronikov; et al. (Instruments, 2024)
The recently demonstrated concept of the plasma photocathode, whereby a high-brightness bunch is initialized by laser ionization within a plasma wakefield acceleration bubble, is informally referred to as Trojan Horse wakefield acceleration. In a similar vein, the dielectric Trojan Horse concept incorporates a dielectric-lined waveguide to support a charged particle beam-driven accelerating mode and uses laser initiated ionization of neutral gas within the waveguide to generate a witness beam. One of the advantages of the dielectric Trojan Horse concept is the reduced requirements in terms of timing precision due to operation at a lower frequency. In this paper, we present experimental results on the generation and characterization of a four-bunch drive train for resonant excitation of wakefields in a cylindrical dielectric waveguide conducted at the Argonne Wakefield Accelerator facility. The results lay the foundation for the demonstration of a plasma photocathode scheme within a dielectric wakefield accelerating structure. Modifications to improve capture efficiency with improved beam transmission are suggested as well.